Importance of 3D and Inkjet Printing For Tony Stark and the Iron Man Suit - Niittynen, Juha; Pakkanen, Jukka (Superhero Science and Technology, 2018)
For decades we have used printers to print superheroes on the pages of comic books but could printing technologies actually be used to print real life superheroes? 3D and functional printing technologies have advanced greatly in recent years and even though these technologies cannot be used to print heroes themselves, they can certainly be used for equipment manufacturing. One character that could or may use 3D printing to rapidly produce prototypes and final versions of new technologies is Tony Stark. As the inventor and primary user of the Iron Man suit, Stark has designed a wearable suit that is not only a weapon but also protects him. However, in battle the suit can become damaged and require urgent repairs. To aid in these repairs, Tony Stark could turn to 3D printing technologies to produce new components for the suit. In this paper we will outline 3D printing technologies and describe their current applications. We will then discuss how 3D printing is being used to print electronics and the ramifications for Tony Stark, his Iron Man suit and the potential use for a real Iron Man suit.